2013
DOI: 10.1074/jbc.m112.429084
|View full text |Cite
|
Sign up to set email alerts
|

The Free Fatty Acid Receptor G Protein-coupled Receptor 40 (GPR40) Protects from Bone Loss through Inhibition of Osteoclast Differentiation*

Abstract: Background: Long chain fatty acids have been shown to activate the membrane-bound receptor GPR40. Results: GPR40 agonist alters bone-resorbing cell differentiation through inhibition of the NF-B system. Conclusion: GPR40 exerts protective effects in vivo on bone tissue. Significance: GPR40 is a nutritional and therapeutic target opening up new avenues for clinical investigations in terms of metabolic and age-related bone disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 38 publications
1
62
0
Order By: Relevance
“…The activation of ERK with subsequent recruitment of the pro-apoptotic factor Bax to the outer membrane of the mitochondria was posited as the cause of TZD-related bone loss (125). In opposition to this mechanism, GW9508, a GPR40 agonist that blocks osteoclast differentiation in vitro , was found to prevent ovariectomy-induced bone loss in wildtype, but not Gpr40 −/− mice (126). …”
Section: Gpr40 and Pparγ An Integrated Two-receptor Signaling Patmentioning
confidence: 99%
“…The activation of ERK with subsequent recruitment of the pro-apoptotic factor Bax to the outer membrane of the mitochondria was posited as the cause of TZD-related bone loss (125). In opposition to this mechanism, GW9508, a GPR40 agonist that blocks osteoclast differentiation in vitro , was found to prevent ovariectomy-induced bone loss in wildtype, but not Gpr40 −/− mice (126). …”
Section: Gpr40 and Pparγ An Integrated Two-receptor Signaling Patmentioning
confidence: 99%
“…The cells were then blocked in 4% nonfat milk and incubated with rabbit polyclonal anti-GPR40 (35,36) at 4°C overnight, followed by incubation for 1 h with FITC-conjugated anti-rabbit IgG. Fluorescence was visualized using a confocal microscope (LSM700, Carl Zeiss Microscopy, Jena, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…26,27 Recently, activation of FFAR1 and FFAR3 by endogeneous or synthetic ligands has been shown to inhibit NF-kB activation in both osteoclasts and macrophages. 19,28 In the light of these data, inhibition of NF-kB signaling pathways may contribute to explain the protective role of GPR40 in OA.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that GPR40 knock-out (GPR40 À/À ) mice exhibited osteoporotic features and that GPR40 stimulation preserved bone mass. 19 Regarding the close relationships between bone and cartilage tissues behavior, the role of GPR40 in cartilage physiopathology was investigated in the present study. First, we performed in vitro experiments to investigate the consequence of GPR40 deficiency on chondrocyte metabolism.…”
Section: Introductionmentioning
confidence: 99%